Processing and characterization of paper-derived Ti3SiC2 based ceramic. Issue 10 (December 2015) - Schultheiß, Jan; Dermeik, Benjamin; Filbert-Demut, Ina; Hock, Nils; Yin, Xiaowei; Greil, Peter; Travitzky, Nahum
Abstract: Porous layers of paper-derived titanium silicon carbide (Ti3 SiC2 ), with a thickness ranging from 300 to 700 µm, were obtained by the heat treatment of preceramic papers containing Ti3 SiC2 as filler particles. The tearing strength of the preceramic papers was provided by cellulose fibers obtained from wood by the kraft pulping process, also described as pulp fibers, and ionic starches. Short pulp fibers with an average length of 657 µm were derived from short fibered hardwood (eucalyptus), while long pulp fibers with an average length of 1665 µm were derived from long fibered softwood (spruce, pine and larch). The fiber length of pulp fibers in the preceramic papers also influenced the microstructure and the properties of the paper-derived Ti3 SiC2 . Preceramic papers fabricated with short pulp fibers exclusively led to an average porosity of 18.6 vol% for the paper-derived Ti3 SiC2, whereas the paper-derived Ti3 SiC2 had an average porosity of 45.3 vol% when preceramic papers with long pulp fibers only were used. The density of the paper-derived Ti3 SiC2 also affected the flexural strength, as could be shown by densifying preceramic papers using a calender. Thereby, the flexural strength of paper-derived Ti3 SiC2 could be increased by more than five times, from 13 MPa to 83 MPa. The purity of the paper-derived Ti3 SiC2 was found to be dependent on the purity of the raw materials and the process cycle, with TiC x and Al2 O3 impurities present in the ceramics.